The attributes of God : an introduction - Bray, Gerald Lewis (Wheaton, Illinois : Crossway, 2021)
"In this addition to the Short Studies in Systematic Theology series, theologian Gerald Bray examines the communicable and incommunicable attributes of God"--
Includes bibliographical references and indexes.
Keywords: God (Christianity) -- Attributes